Pemanfaatan Teknologi Suno AI untuk Pengembangan Musik dan Cerita Anak di Taman Kanak-Kanak - Afni Nia Sari; Elvira Sawitri; Rizalina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity aims to introduce and implement the use of Suno AI technology in developing learning media in the form of children's music and stories within the kindergarten environment. The primary issue faced by the partner institution is the limited resources for creating engaging teaching materials that are suitable for early childhood developmental stages. Through a training and mentoring approach, kindergarten teachers were provided with knowledge and practical skills in using Suno AI to produce children's songs and interactive stories relevant to classroom learning themes. The results of the activity show that this technology significantly aids in enhancing teacher creativity and enriching classroom learning media. The children also demonstrated high enthusiasm for the generated songs and stories, which positively impacted their learning motivation and language development. This activity provides tangible contributions to the utilization of AI-based technology in supporting creative and enjoyable early childhood education.